Smart agricultural system for crop monitoring and soil analysis - Das, Bristy; Ul Hoq Sayor, Tahmid Zarif; Nijhum, Rubyat Jahan; Tishun, Mehnaz Tabassum (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.